Reconceptualizing emotional intelligence - Ortinero, Aniceta M. (Education Quarterly, 1992)
This paper reconceptualizes emotional intelligence as used in current psychological discourse. An attractive term, emotional intelligence, popularly called EQ is shown through critical analysis to be a conceptual fallacy. Definition, analysis and exposition of concepts and theories of emotion and intelligence are here given towards elucidating them before being combined for a new meaning. Hence, rather than emotional intelligence, the integrated faculty competencies (IFC or FO) is proposed here which consists of the powers of the will, affection/feeling and the senses under the governance of reason. The study indicates that only the proper coordination of the faculties would generate life skills and values desirable for one's personal success and general well-being.